Advancements in Animal Nutrition an Insights from Veterinary Science - G, Prabakar; L., Arun; Kumaravel, P.; Chahande, Jiwan M; Majumder, Jayeeta; Gangopadhyay, Sourav; Biswas, Susmi; Ganai, Imran Ahmad; Deka, Ilakshy (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Animal nutrition plays a crucial role in the health, well-being, and productivity of livestock and companion animals. As advancements in science and technology continue to reshape the field of animal nutrition, veterinary professionals are at the forefront of translating research findings into practical solutions for optimizing animal health and performance. This journal article provides a comprehensive overview of recent developments and emerging trends in animal nutrition, with a focus on veterinary perspectives. Drawing upon a synthesis of recent studies and industry developments, this paper explores novel dietary approaches, innovative feed additives, and advancements in nutritional science that are transforming the way we feed and care for animals. From precision nutrition and personalized feeding regimens to the use of alternative protein sources and sustainable feed production methods, the article delves into the diverse strategies being employed to address the nutritional needs of a wide range of animal species, the paper examines the role of veterinary professionals in navigating the complexities of animal nutrition and promoting optimal health outcomes for their patients. By staying abreast of the latest research findings and leveraging their expertise in clinical practice, veterinarians play a vital role in formulating customized nutritional plans, managing dietary-related health conditions, and promoting responsible feeding practices among animal owners. Through a critical analysis of key challenges and opportunities, this study aims to inform veterinary practitioners, researchers, and industry stakeholders about the current state of the art in animal nutrition and stimulate further interdisciplinary collaboration and innovation in this rapidly evolving field. By embracing new technologies, advancing scientific knowledge, and prioritizing animal welfare, the veterinary community can continue to drive positive change and improve the nutritional well-being of animals worldwide.